Amref Alternative Rites of Passage (ARP) model for female genital mutilation/cutting, teenage pregnancies, and child, early and forced marriages in Kenya: - Esho, Tammary C.; Scholten, Julia; Conradi, Hilke; Kawai, David; Mbogo, Bernard; Lugayo, Denge; Opanga, Yvonne; Muhula, Samuel; Matanda, Dennis Juma (My University, 2023)
The Amref Alternative Rites of Passage (ARP) model was initiated in 2009. To date, about 20,000 girls have been supported by their communities to denounce female genital mutilation/cutting (FGM/C) and graduate into ‘maturity’ through ARP. While this intervention has been implemented for decades, there is limited evidence of its effectiveness in ending FGM/C. In order to ascertain the effectiveness of this intervention, Amref has developed a digital tracking tool to follow up on girls who have and haven’t gone through the ARP. The key research question is: what effect does ARP have on incidences of FGM/C, teenage pregnancy and child, early and forced marriages among adolescent girls and young women?
a stepped-wedge cluster randomised controlled trial protocol
Keywords: Female Genital Mutilation--Cutting; Alternative Rites of Passage; Alternative Rites of Passage, Nairobi, Kenya